Centrosome‐mediated microtubule remodeling during axon formation in human iPSC‐derived neurons. (9th April 2021) - Lindhout, Feline W; Portegies, Sybren; Kooistra, Robbelien; Herstel, Lotte J; Stucchi, Riccardo; Hummel, Jessica J A; Scheefhals, Nicky; Katrukha, Eugene A; Altelaar, Maarten; MacGillavry, Harold D; Wierenga, Corette J; Hoogenraad, Casper C
Abstract: Axon formation critically relies on local microtubule remodeling and marks the first step in establishing neuronal polarity. However, the function of the microtubule‐organizing centrosomes during the onset of axon formation is still under debate. Here, we demonstrate that centrosomes play an essential role in controlling axon formation in human‐induced pluripotent stem cell (iPSC)‐derived neurons. Depleting centrioles, the core components of centrosomes, in unpolarized human neuronal stem cells results in various axon developmental defects at later stages, including immature action potential firing, mislocalization of axonal microtubule‐associated Trim46 proteins, suppressed expression of growth cone proteins, and affected growth cone morphologies. Live‐cell imaging of microtubules reveals that centriole loss impairs axonal microtubule reorganization toward the unique parallel plus‐end out microtubule bundles during early development. We propose that centrosomes mediate microtubule remodeling during early axon development in human iPSC‐derived neurons, thereby laying the foundation for further axon development and function. Synopsis: This study shows that axon formation critically relies on centrosome function in human neurons. Centrosomes mediate the remodeling of the microtubule network in developing axons, which is important for axon development and function at later stages. Centrosomes display microtubule organizing functions during the onset of axon formation in human neurons. Trim46 localization shifts from centrosomes to axons during development of human neurons. Centriole loss in human neuronal stem cells affects subsequent axon development, as shown by defects in action potential firing, Trim46 localization and growth cone morphologies. Centriole loss perturbs the remodeling of the unique microtubule network in axons of human neurons during early development. Abstract : Live‐cell imaging of centriole‐depleted cultured neurons demonstrates the essential role of human centrosomes in regulating various aspects of axon maturation and function via microtubule network reorganization.